Multivitamins for the Prevention of Cardiovascular Disease in Men - Rizzo, Toni (MD Conference Express, 2012)
Basic research has suggested that some individual vitamin and mineral components of multivitamins might reduce the risk of cardiovascular disease. However, no large-scale, long-term randomized trials have tested the effect of multivitamins. This article presents results from the Physicians' Health Study II (PHS II) on the long-term risks and benefits of multivitamin use in male physicians [Sesso HD et al. JAMA 2012].